CONSTITUTIONAL CRISES IN DEMOCRACIES: AN OPERATIONAL VIEW - Nitin Gahlot; Dr. Ajeet Singh (IJRDO - Journal of Social Science and Humanities Research, 2026)
The development of constitutional democracy has been a striking component, however, during the last decade it has experienced a dramatic downfall. That decline is stamped less by established vote-based systems being ousted than by an expansion in systems that hold the formal institutional trappings. In well-known conversation, the term constitutional crisis is utilized to depict each sort of contention, great and little. Yet, we want to give the thought more prominent scientific lucidity, and all the while, make a few significant focuses about constitutional design. The secret, we will contend, is to ponder emergency not as far as constitutional disagreement but rather as far as constitutional design. Conflict and struggle are normal elements of politics. The objective of constitutions is to oversee them inside adequate limits. Whenever constitutional design works appropriately - regardless of whether individuals firmly can’t help contradicting one another and compromise one another - there is no crisis. Then again, when the arrangement of constitutional design separates, either because individuals leave it or because it is driving them off the so-called precipice, conflicts and dangers take on an exceptional direness that merits the name of crisis. This research paper contends that answers for the contemporary crisis can’t be seen exclusively by reinforcing liberal organizations; to get by constitutional design should likewise try to revive its democratic expectations.